2016
DOI: 10.1115/1.4034966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Temperature and Humidity on Combustion and Emissions of a Spark-Assisted Compression Ignition Engine

Abstract: Spark-assisted compression ignition (SACI) offers more practical combustion phasing control and a lower pressure rise rate than homogeneous charge compression ignition (HCCI) combustion and improved thermal efficiency and lower NOx emissions than spark ignition (SI) combustion. Any practical passenger car engine, including one that uses SACI in part of its operating range, must be robust to changes in ambient conditions. This study investigates the effects of ambient temperature and humidity on stoichiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There are numerous studies, which investigated the effect of relative humidity on real-life engines. For example, Chang et al [5] showed that a 50% increase in relative humidity from ambient at 30% to a mild at 60% had a significant impact on the engine manifested mainly in retarding the combustion phasing along with reducing the NOx concentration. Similarly, Pekula et al [6] showed that a threefold increase in the relative humidity can cause a reduction of NOx concentration by 15 to 20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies, which investigated the effect of relative humidity on real-life engines. For example, Chang et al [5] showed that a 50% increase in relative humidity from ambient at 30% to a mild at 60% had a significant impact on the engine manifested mainly in retarding the combustion phasing along with reducing the NOx concentration. Similarly, Pekula et al [6] showed that a threefold increase in the relative humidity can cause a reduction of NOx concentration by 15 to 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 5. Raman spectra of the different zinc, iron and mixed zinc and iron phosphate glasses used as standards for Raman spectroscopy…”
mentioning
confidence: 99%
“…Similarly, elevating Tintake also increases the values of HRRmax because of a smaller fraction of MFBtrans. 23 The cyclic variation of CoV of HRRmax is also given in Figure 10. Similar to the trends in the variation of MFBtrans, the variation in HRRmax decreases with both advancing ST and increasing Tintake.…”
Section: Resultsmentioning
confidence: 99%
“…With the perspective on the SICAI combustion and studies mentioned above, it is seen that SICAI combustion is very sensitive to the in-cylinder dilution rate and thermal state. 23 Besides, the effect of spark assistance relies heavily on the in-cylinder condition and the operating load. 24,25 Several studies have shown the role of varying spark timings (STs) in the control of SICAI combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this only affect the CAFE standard and it is not the fuel economy ratings which would inform the consumer or the emission level certification. [16] While Europe and China have the similar evaluation method for fuel economy, commissions from these countries established the Real Driving Emissions (RDE) regulations and announced that the vehicle emission must be tested on the road in addition to the drive cycle testing and must be measured with a Portable Emission Measurement System (PEMS) [17]- [19]. However, the reproducibility of these tests is very difficult to achieve because of the dynamic and environmental boundaries such as routes, ambient conditions, and the data analysis methods.…”
Section: Introductionmentioning
confidence: 99%